2008
DOI: 10.4028/www.scientific.net/jnanor.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding: A Bottom-Up Approach for the Synthesis of Films Composed of Gold Nanoparticles

Abstract: Abstract. Citrate gold nanoparticles of 13.5 nm average diameters have been synthesized by Turkevich method and further functionalized by place exchange reaction using mercaptosuccinic acid (MSA), 1,4-benezenedimethanethiol (1,4BDMT) or mercaptoundecanoic acid (MUA) as the incoming ligands. In the first case, the functionalization of the gold clusters with MSA yielded solution of blue color and large aggregates on carbon grids. Moreover, after filtration and drying, any film formed by hydrogen bonding, could n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moreover, they have shown that electron transfer kinetics depends strongly on the orientation of the nanotubes, being faster for vertically aligned nanotubes than for randomly disperse nanotubes. , Diao et al showed that the electrochemical process tends to be more reversible when the density of the nanotubes is increased by allowing a longer assembly time . In consequence, the electrochemical properties of the anisotropic nanomaterials seems to be dependent on more parameters than in the case of spherical nanoparticles, for which mainly the size and the stabilizing ligands prove to have a high influence on their chemical and electrochemical properties. Concerning the gold nanorods, many authors have focused their research efforts on the optical properties of these nanomaterials, their surface modification, or on the study of their self-assembly within stable networks with well-defined features, and to our knowledge, there are no studies related to their electrochemical properties. The construction of AuNR assemblies was based either on electrostatic interaction, hydrophilic−hydrophobic interaction, or specific interactions such as antigen−antibody, oligonucleotides, biotin-streptavidin, or aptamer−protein, showing that the AuNRs are assembled in either end-to-end (EE) or side-by-side (SS) orientations. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have shown that electron transfer kinetics depends strongly on the orientation of the nanotubes, being faster for vertically aligned nanotubes than for randomly disperse nanotubes. , Diao et al showed that the electrochemical process tends to be more reversible when the density of the nanotubes is increased by allowing a longer assembly time . In consequence, the electrochemical properties of the anisotropic nanomaterials seems to be dependent on more parameters than in the case of spherical nanoparticles, for which mainly the size and the stabilizing ligands prove to have a high influence on their chemical and electrochemical properties. Concerning the gold nanorods, many authors have focused their research efforts on the optical properties of these nanomaterials, their surface modification, or on the study of their self-assembly within stable networks with well-defined features, and to our knowledge, there are no studies related to their electrochemical properties. The construction of AuNR assemblies was based either on electrostatic interaction, hydrophilic−hydrophobic interaction, or specific interactions such as antigen−antibody, oligonucleotides, biotin-streptavidin, or aptamer−protein, showing that the AuNRs are assembled in either end-to-end (EE) or side-by-side (SS) orientations. …”
Section: Introductionmentioning
confidence: 99%
“…Afterward, a mixture of 50 μL of AuNPs (9.75 nM) with 10 μL of aptamer S12 (0.4 μM) and 10 μL of different (PP) concentrations incubated with gentle rotation for 60 min at 25 °C. Then, 30 μL of NaCl (150 mM) was added and the change of color and spectrum were determined by the naked eye and UV–vis spectrophotometer . The concentration of PP was plotted against 625/520 absorbance ratio.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Then, 30 μL of NaCl (150 mM) was added and the change of color and spectrum were determined by the naked eye and UV−vis spectrophotometer. 59 The concentration of PP was plotted against 625/520 absorbance ratio. The homologous peptide (NPY) and BSA were also examined at the same conditions to test the specificity of the developed sensing platform.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%